THE APPLICATION OF THE STUDENT FACILITATOR AND EXPLAINING (SFE) MODEL TO IMPROVE STUDENT LEARNING OUTCOMES IN GIVING ANNOUNCEMENT MATERIALS IN CLASS X MIPA 2 SMA NEGERI 1 PURI - Slamet Hariadi (Sean Institute, 2022)
English is a subject that focuses on preparing for the era of globalization. The results of initial observations at SMA Negeri 1 Puri obtained daily test scores for class X MIPA 2 . More than 50% did not complete in learning. The number of students who have not completed is 12 students with a completeness percentage of 60%. Based on the description, it shows that the learning outcomes of giving announcement material do not reach the minimum completeness criteria. The low learning outcomes are due to the application of learning models that are not suitable, students are passive in learning, there is no assessment of assignments. The purpose of this study was to analyze the increase in learning outcomes for class X MIPA 2 SMA Negeri 1 Puri, through the application of the Student facilitator and explaining (SFE) learning model. To improve student learning outcomes in the material giving announcement, a class action research was conducted which consisted of two cycles. Each cycle consists of stages of planning, implementation, observation and reflection. The subjects of this study were students of SMA Negeri 1 Puri Class X MIPA 2 academic year 2016/2017 which consisted of 28 students. The data collection instrument in this study was a matter of evaluation for the cognitive domain which was carried out at the end of each cycle. learning outcomes, and can teach and train students' character behavior. The implementation of the lesson plans was categorized as good with an average score of 3.0 in the first cycle and 3.27 in the second cycle. Student activity reached 85.26% in the first cycle and increased to 92.22%. In the aspect of scientific behavior, both cycles show that they are in the good category. Mastery learning outcomes also showed an increase, from 75% in the first cycle to 92.86% in the second cycle.